2019
DOI: 10.1007/s11242-019-01250-w
|View full text |Cite
|
Sign up to set email alerts
|

Foam Generation, Propagation and Stability in Porous Medium

Abstract: There have been several foam field applications in recent years. Foam treatments targeting gas mobility control in injectors as well as gas blocking in production wells have been performed without causing operational problems. The most widely used injection strategy of foam has been injecting alternating slugs of surfactant in brine with gas injection. This procedure seems to be beneficial as injection is easy to perform and control below fracturing pressure. Simultaneous injection of surfactant solution and g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 91 publications
0
26
0
2
Order By: Relevance
“…Regarding the non-uniform distribution size of the gas bubbles, large bubbles have lower pressure than small bubbles which can cause the chemical differences. Therefore, the gas would diffuse into the liquid phase from smaller to larger bubbles that have caused the coalescence [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the non-uniform distribution size of the gas bubbles, large bubbles have lower pressure than small bubbles which can cause the chemical differences. Therefore, the gas would diffuse into the liquid phase from smaller to larger bubbles that have caused the coalescence [29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…Field applications of foam for EOR (Skauge et al 2020) (EDS) elemental analysis techniques, it was found that the blocking mechanism of PMs in the throat and cracks of cores is mainly manifested in three aspects: adsorption retention, mechanical retention and agglomeration. By dispersing nanoparticles in low-salinity water, most problems associated with rock/fluid interactions can be eliminated by improving the attractive force between fine particles and the particle surface (Arab and Pourafshary 2013) and preventing formation damage (Abhishek et al 2018).…”
Section: Fig 11mentioning
confidence: 99%
“…The foamability and foam stability were tested using the Waring blender method at ambient temperature and atmospheric pressure. [40][41][42][43] The solution was rstly prepared with a mixture of formation water, SDS and HPAM. The concentration of SDS ranged from 0.1 wt% to 0.6 wt%, and the concentration of HPAM ranged from 0.1 wt% to 0.5 wt%.…”
Section: N 2 -Foam Evaluation Experimentsmentioning
confidence: 99%